Предмет: Алгебра,
автор: Чайник01
(2x-5)(2x+5)-(x-3)(x+7)=0
Ответы
Автор ответа:
1
(2x - 5)(2x + 5) - (x - 3)(x + 7) = 0
4x² - 25 - x² - 7x + 3x + 21 = 0
3x² - 4x- 4 = 0
D = (- 4)² - 4 * 3 * (- 4) = 16 + 48 = 64 = 8²
4x² - 25 - x² - 7x + 3x + 21 = 0
3x² - 4x- 4 = 0
D = (- 4)² - 4 * 3 * (- 4) = 16 + 48 = 64 = 8²
Похожие вопросы
Предмет: Русский язык,
автор: yasminsadykova52
Предмет: Математика,
автор: ssatabekovna56
Предмет: Литература,
автор: kamilladanil7
Предмет: Математика,
автор: dimmackarow201